2023
DOI: 10.3390/ijms24021186
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ANO1 by Cis- and Trans-Resveratrol and Their Anticancer Activity in Human Prostate Cancer PC-3 Cells

Abstract: Anoctamin1 (ANO1), a calcium-activated chloride channel, is involved in the proliferation, migration, and invasion of various cancer cells including head and neck squamous cell carcinoma, lung cancer, and prostate cancer. Inhibition of ANO1 activity or downregulation of ANO1 expression in these cancer cells is known to exhibit anticancer effects. Resveratrol, a natural polyphenol abundant in wines, grapes, berries, soybeans, and peanuts, shows a wide variety of biological effects including anti-inflammatory, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In a recent study, RSV in both its cis and trans forms was shown to inhibit the activity of the Anoctamin1 (ANO1) channel (a calcium-activated chloride channel, which is involved in the proliferation, migration, and invasion of various types of cancer, including head and neck squamous cell carcinoma, lung cancer, and prostate cancer) (Carter et al, 2014). In addition, they showed how RSV also decreased the expression of ANO1 protein and mRNA in PC-3 prostate cancer cells (Jeon et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…In a recent study, RSV in both its cis and trans forms was shown to inhibit the activity of the Anoctamin1 (ANO1) channel (a calcium-activated chloride channel, which is involved in the proliferation, migration, and invasion of various types of cancer, including head and neck squamous cell carcinoma, lung cancer, and prostate cancer) (Carter et al, 2014). In addition, they showed how RSV also decreased the expression of ANO1 protein and mRNA in PC-3 prostate cancer cells (Jeon et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…The trans-isomer is more stable and predominant, with more therapeutic properties [ 63 ]. Cytotoxicity studies on pancreatic cancer, breast cancer, small-cell lung carcinoma, colon cancer, and prostate cancer cell lines revealed that trans-resveratrol possesses slightly more potent cytotoxic properties than the cis-isomer, attributed to its better bioavailability and biodistribution [ 64 , 65 , 66 ]. Upon exposure to sunlight or UV radiation at 254 nm or 366 nm, trans-RSV converts into cis-RSV and vice versa.…”
Section: Resveratrolmentioning
confidence: 99%
“…Stilbenoids are important phytoalexins that protect plants from pathogens [1]. Moreover, stilbenoids exhibit a number of health-promoting benefits, namely antioxidant, antiinflammatory, anticancerogenic, antiatherogenic, antiviral, and neuroprotective activities [2][3][4][5][6][7][8]. Stilbenoids are found in only a few plant families, including Vitaceae, Fabaceae, Polygonaceae, and Gnetaceae [9][10][11].…”
Section: Introductionmentioning
confidence: 99%